Driving ta'awun and ukhuwwah through Malaysia Madani values in workplace diversity - Mhd. Sarif, Suhaimi; Yahya, Rohaziah; Firmansah, Yayan (Zes Rokman Resources, 2025)
This study explored how Islamic principles of ta’awun (collaborative synergy) and ukhuwwah (fraternal solidarity) could foster resilient, inclusive workplace cultures when embedded within the Malaysia Madani framework, particularly within Islamic universities in Southeast Asia. Through focus group discussions, the study argued that shared moral commitment, cultural empathy and mutual purpose contributed to institutional unity. The six core values of Malaysia Madani—sustainability, prosperity, innovation, respect, trust, and compassion—served as ethical foundations that shaped behaviour and reinforced bonds among teams. However, operationalising these abstract Islamic principles within real-world organisational practices proved challenging. Translating these values into actionable strategies in multicultural workplaces required overcoming significant gaps between theoretical applications and day-to-day implementation. The study also identified issues regarding the adaptability of Islamic principles in secular, pluralistic environments, with some staff members expressing concerns about the potential alienation of non Muslim stakeholders. Additionally, the study’s reliance on qualitative data from a narrow academic context raised questions about the generalisability of its findings. To address these challenges, future research should adopt a mixed-methods approach to validate these insights across diverse organisational types and cultural settings. Longitudinal studies and comparative research could further explore the adaptability and impact of Islamic value-based management.